Florida's Fabulous Forests - Martha C. Monroe; Allison W. Bowers (EDIS)
The Forestry Florida's Fabulous Forests Project Book (4HFOM13) is the third 4-H Project Book in the Forest Resources series and for youth ages 12-18. It includes 17 engaging activities (each with reflective questions) and 47 ideas for additional projects and challenges. Youth explore 10 different kinds of forests in Florida: 8 natural ecosystems, the urban forest, and pine plantations. The activities also lead youth through an understanding of forest management, forest systems (wildlife, water, and soil), and forest management issues: wildfire and prescribed fire, forest insect and diseases, and invasive exotic plants. First published May 2001.